Analisis Putusan Nomor 239/Pdt.G/2015/Pn.Jkt.Pst Ditinjau Dari Aspek Kepastian Hukum Dan Keadilan Dalam Pembagian Waris Beda Agama - Rayi Kharisma Rajib; Nafis Khairina; Simontaro Halezky Sinaga (CV. ITTC INDONESIA, 2026)
Indonesia adheres to a plural inheritance law system, namely the Civil Code (Western inheritance law), customary law, and the Compilation of Islamic Law (KHI). This pluralism creates complex problems when the testator and heirs have different religious backgrounds. Decision of the Central Jakarta District Court Number 239/Pdt.G/2015/PN.JKT.PST is a clear example of the complexity of cross-religious inheritance issues in Indonesian judicial practice. This study aims to analyze the legal considerations of the judge in the decision and evaluate them from the aspects of legal certainty and justice. The method used is normative juridical legal research with a case study approach, supported by interviews with judges and legal academics. The results of the analysis show that the judge erroneously applied Western inheritance law (Civil Code) in a case that should have been subject to the Compilation of Islamic Law, given that both the testator and his third wife as the first plaintiff were Muslim. This error resulted in a decision that did not meet the standard of legal certainty and did not reflect justice for the first plaintiff. The lawsuit should have been filed with the Religious Court, not the District Court.